Effectiveness of implementing evidence-based approaches to promote physical activity in a Midwestern micropolitan area using a quasi-experimental hybrid type I study design - Barbara Baquero; Nicole Novak; Daniel K. Sewell; Christine M. Kava; Jason Daniel-Ulloa; Hanh Pham; Natoshia Askleson; Sato Ashida; Helena Laroche; Adriana Maldonado Gonzalez; Rebecca Bucklin; Heidi Haines; et al. (BMC, 2024)
Abstract Background Much evidence-based physical activity (PA) interventions have been tested and implemented in urban contexts. However, studies that adapt, implement, and evaluate the effectiveness of these interventions in micropolitan rural contexts are needed. The study aimed to evaluate the effectiveness of the Active Ottumwa intervention to promote PA in a micropolitan community. Methods Between 2013 - 2019, we implemented Active Ottumwa in a micropolitan setting, and subsequently implemented and evaluated its effectiveness using a Hybrid Type I design. In this paper, we describe the intervention's effectiveness in promoting PA. We collected PA data over 24 months from a cohort of community residents using accelerometers and PA data from two cross-sectional community surveys administered in 2013 and 2018, using the Global Physical Activity Questionnaire. Results From the cohort, we found significant change in PA over 24 months (P = 0.03) corresponding to a 45-min daily decrease in sedentary activity, a daily increase of 35-min in light PA and 9 min in moderate-to-vigorous PA. There was a statistically significant (P = 0.01) increasing trend at the population-level in the moderate-to-vigorous composition of 7 min between the two cross-sectional assessments (95% CI: 0.1%-1.34%). Conclusions The study demonstrates that the adapted evidence-based PA interventions in a micropolitan context is effective.